Pengaruh Diskon Harga, Kualitas Layanan, Dan Citra Perusahaan Terhadap Keputusan Penggunapada Jasa Pengiriman Shopee Express Di Kota Kediri - Refan Hardiansyah; Erwin Syahputra; Iing Sri Hardiningrum (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the influence of price discounts, service quality, and company image both partially and simultaneously on user decisions on the Shopee Express delivery service in Kediri City. The population in this research is all consumers who have made transactions in the last week at Shopee Express, Kediri City, totaling 1650 consumers. The sample in this study was obtained using the Slovin formula with a sample size of 95 respondents. Data sources were obtained by means of observation, interviews, documentation, questionnaires and literature. This research data measurement uses a Likert scale. The analysis technique uses multiple linear regression analysis with the SPSS IBM 26 application. The results of this research show that the price discount variable has a significant effect on user decisions. The service quality variable is significant in user decisions. The company image variable has a significant effect on user decisions. And the variables of price discount, service quality, and company image simultaneously have a significant influence on user decisions.